Pengaruh Upright Position terhadap Lama Persalinan Kala 1 Fase Aktif - Sumastri, Heni; Rahmaninda, Dwiana AS; Vasra, Elita; Hendawati, Hendawati (Poltekkes Kemenkes Palembang, 2023)
Background: Prolonged labor in the active phase of first stage increase discomfort on birthing mother, including experience more pain, anxiety, and fatigue. The discomfort during labor can be decreased by doing a birthing position. This study aims to determine the effect of upright position on the length of labor in the active phase of first stage. Methods: The study used a quasi-experimental posttest only design with control group. A total of thirty birthing mothers in the active phase of first stage became the subject of the study. Subjects were grouped into two: the upright position group (n=15) and the control group (n=15). The upright position group regularly performed an upright position, including squatting and standing during the active phase of first stage labor. The control group was not directed to perform the upright position. The length of labor in the active phase of first stage between two groups was compared when the cervical dilatation reached 10 cm (complete cervical dilatation). Results: Upright position significantly affected the length of labor in the active phase of first stage, p-value=0,009 (<0,05). There were twelve subjects (80%) of upright position group experienced the length of labor in the active phase of first stage less than six hours (fast category). Meanwhile, in the control group, there were only three subjects experienced the length of labor in the active phase of first stage in fast category. Conclusion: The upright position performed by birthing mother has a posiive effect, namely accelerate the duration of labor in the active phase of first stage. Keywords : Upright Position, Length of Labor, The Active Phase of First Stage Labor.